ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SELAMA PANDEMIC COVID-19 PADA PT WILMAR CAHAYA INDONESIA - Novyan Muhammad Arif; Agustina Prativi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study focuses on comparing the financial performance of PT Wilmar Cahaya Indonesia before and during the Covid-19 virus pandemic using profitability ratio analysis. The profitability ratio is an industry indicator to manifest profit based on its sales, assets, and liabilities. There are several types of ratios, namely Gross Profit Margin, Net Profit Margin, Return On Equity, and Return On Assets. This type of research data uses quantitative data centered on the Financial Statements of PT Wilmar Cahaya Indonesia from 2018 to 2021. The data source of this research uses secondary data and the method of retrieval is using library research techniques. The results of the ratio analysis carried out in this study prove that relevant changes were found in the condition of financial performance before and during the Covid-19 pandemic.